Étude théorique de quelques hydrures métalliques - SMAIN, Tahar (Université de Laghouat , Bibliothèque centrale, 2021)
Structural, electronic and lattice dynamical properties, using FP-LAPW and PW-PP techniques, within density functional theory, are investigated for the compounds LaMgNi4Hx, YMgNi4Hx with(x = 0, 1,4 and 7) in cubic phases. The structural parameters are in good agreement with both experimental and theoretical results. The calculated cohesive energy and the formation enthalpy are negative for this structure, the YMgNi4H has good thermodynamic stability. The calculated band structure indicates that all structures have a metallic behavior. The Electron density shows strong covalent interactions between Mg–H and metallic interactions between Y–Ni elements. From calculated elastic constants, mechanical properties and the dispersion of the phonons within DFPT, we found that all structures are mechanically stable.The thermodynamic properties as a function of temperature were calculated in the range of [0, 2000] K◦.